Estimated radiation doses to different organs among patients treated for ankylosing spondylitis with a single course of X rays. - Lewis, C; Smith, P; Stratton, I; Darby, S; Doll, R (1988)
A follow-up study of over 14,000 patients treated with a single course of X rays for ankylosing spondylitis demonstrated a substantial excess risk of developing cancer. Previously the excess risk of leukaemia has been related to the estimated mean radiation dose to the active bone marrow but detailed estimates were not made of the radiation doses to other organs. In the present work, data extracted from the original treatment records of a random sample of one in 15 patients have been used to make dose estimates, using Monte Carlo methods, for 30 specific organs or regions of the body and 12 bone marrow sites. Estimates of the mean and median organ doses, standard deviations and ranges have been tabulated. Detailed distributions are presented for six organs (lung, bronchi, stomach, oesophagus, active bone marrow and total body). Comparison with the earlier bone marrow estimates and more recent theoretical estimates shows good agreement.